PEMPROSESAN DAN ANALISIS BIG DATA: PELUANG DAN TANTANGAN DALAM DUNIA INDUSTRI - Retno Paluvi; Muhammad Irwan Padli Nasution (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Big data processing and analysis have become crucial in the digital era, especially in the rapidly evolving industrial sector. Big data plays a strategic role in decision-making and operational efficiency. This study discusses the application of big data in industry while identifying the main opportunities and challenges involved. The findings reveal that big data can enhance competitiveness, streamline business processes, and enable more personalized services. However, challenges such as complex infrastructure requirements, limited skilled personnel, and issues of privacy and data security remain significant barriers.